Encapsulation of ascorbyl palmitate in maize granular starch through an irradiation–hydrothermal method. (July 2023) - Yan, Huili; Cui, Long; Wang, Xian; Zhang, Dong; Feng, Wenhao; Chen, Yuntang
Abstract: In this study, maize starch treated with γ radiation (0–10 kGy) was used to prepare maize granular starch-ascorbyl palmitate (MGS-AP) complexes by a hydrothermal method. The MGS-AP complex encapsulation efficiency and physicochemical properties were evaluated. The irradiation effect on starch chain degradation increased the percentage of ascorbyl palmitate (AP) encapsulated in the starch and considerably raised the Rapid Visco Analyzer (RVA) profile viscosity in the later cooling stage. With increasing irradiation dose, the MGS-AP complex swelling power, relative crystallinity and thermal stability gradually increased, and the antioxidation activity first decreased and then increased, with a minimum value at 1 kGy. Generally, the MGS-AP complexes had relatively high encapsulation efficiencies, and a complex with the highest swelling power, crystallinity, shearing resistance, antioxidation activity and thermal stability was obtained with 10 kGy irradiation. This study provides a basis for preparing granular starch-AP complexes with a relatively high encapsulation efficiency and stability. Highlights: An irradiation-hydrothermal method was used to prepare MGS-AP complexes. Encapsulation efficiency of MGS-AP complexes increased after irradiation. The RVA profile of the complex in the later cooling stage shifted with irradiation. Swelling power and thermostability of the complex increased with irradiation dose. The complex with an irradiation dose of 10 kGy had the highest antioxidant activity.